Lean Six Sigma Application to Improve Sub-Process Failure Repair in Communication Links - Ticona Gregorio, Hugo Iván (2022)
The troubleshooting process for communication links in telecommunications is a complex process that is divided into sub-processes; one of these sub-processes is Failure Repair. In this paper, Lean Six Sigma is applied in to improve this sub-process. As a result, the monthly average of the Repair Time (TR) improved in 36.7%, and the Repair Time Yield (YTR) improved in 300.08%.